Integrative transcriptomic and metabolomic analysis reveals the effects of a sudden drop in salinity on osmoregulation, metabolism, anti-oxidation, and immunity in Eriocheir sinensis megalopa and juvenile stages - Mingjun Shen; Yue Wang; Fei Zhu; Mingliang Wei; Dafeng Xu; Caojin Zhang; Shuran Du; Jianbin Jiang; Jianlou Zhou; Zhiyong Zhang; Yongkai Tang; Zhiwei Zhang; et al. (Aquaculture Reports, 2023)
Eriocheir sinensis has a special habit of migrating from marine to freshwater during its larval developmental stage. Salinity is an important environmental factor affecting the survival rate and growth performance of its larvae. Currently, the molecular mechanisms involved in the adaptation of E. sinensis larvae to a hyposaline environment remain unclear. Therefore, in this study, we designed an acute hyposaline stress experiment and sequenced the transcriptome and metabolome of the treated samples. After screening and annotation, 3323 and 2874 differentially expressed genes and 273 and 334 differentially expressed metabolites were identified by analysis of the transcriptomic data and metabolomic data at the megalopa and juvenile stages, respectively. Subsequently, a combined analysis of pathways was performed by co-mapping differentially expressed genes and differentially expressed metabolites into a KEGG database. Furthermore, the analysis results showed that 92 and 115 shared KEGG pathways were identified at the megalopa and juvenile stages, respectively. These shared pathways were mainly related to energy metabolism, osmotic pressure regulation, antioxidants, and immunity. The results showed that megalopa and juvenile had similar response mechanisms for adjusting to extremely hyposaline environments. The sudden drop in salinity may have impaired the osmoregulation ability and disturbed the energy metabolism of E. sinensis larvae. The glucose and TCA cycle processes were inhibited, and the cholesterol and glycine metabolisms were significantly changed. In addition, the sudden drop in salinity may cause oxidative stress in the larvae, accelerate the synthesis and consumption of glutathione, damage mitochondrial function, and induce cell apoptosis. Therefore, this study provides key information for understanding hyposaline tolerance mechanisms in E. sinensis larvae.